A driftless gas proportional scintillation counter for muonic hydrogen X-ray spectroscopy under strong magnetic fields - Veloso, J. F. C. A. (2001)
An experiment involving muonic hydrogen requires an X-ray detector having large area and working under strong magnetic fields (5 T) with good energy and timing resolution. A compact, driftless gas proportional scintillation counter (GPSC) capable of operating under such magnetic fields is investigated. This GPSC uses a CsI photocathode deposited onto a microstrip plate as the UV scintillation readout photosensor. This photocathode has the advantage of operating in direct contact with the scintillation gas. The detector is filled with pure xenon and is designed to have a high detection efficiency for 2 keV X-rays. Energy resolutions of 23% and 22% were obtained for 1.74 and 2.3 keV X-rays, respectively. The low-energy detector limit due to the electronic noise is 300 eV. Its performance in the presence of strong magnetic fields was tested. At magnetic field of 5 T the detector pulse amplitudes are reduced by less than 25%, while the detector energy resolution and pulse rise time present a relative increase of less than 10%.